(untitled) (Jurnal Manajemen Bisnis, 2026)
This study aimed to analyze the influence of celebrity endorsements, specifically the dimensions of trustworthiness, expertise, and attractiveness, on consumers’ purchase interest at Gallery Phone Makassar. A quantitative research design was employed, using a survey to gather primary data from the consumer population. The data were analyzed using Partial Least Squares Structural Equation Modeling to evaluate the structural relationships among the variables and test the research hypotheses. The results revealed that trustworthiness, expertise, and attractiveness each had a significant positive effect on purchase interest. Among these dimensions, attractiveness and expertise emerged as the most dominant factors in attracting attention and influencing consumer perceptions toward mobile technology products. These findings suggest that consumers are highly influenced by a celebrity’s visual appeal and perceived technical competence when forming interest in purchasing a smartphone. This study provides practical insights for marketers to optimize their digital marketing strategies by selecting influencers who strike a strong balance between aesthetic appeal and professional credibility, thereby effectively driving purchase interest.